2022
DOI: 10.32479/ijeep.13125
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth, Population, and Policy Strategies : Its Effects on CO2 Emissions

Abstract: This research work has been focused on China and India. Both Countries has a big number in population in the world and the rate of economic growth has been increasing every year. However, this is still accompanied by air pollution (CO2 emissions). Therefore, this study aims to analyze the relationship of population and GDP to CO2 emissions in China and India in the 1984-2014 timeframe and provide policy recommendations related to the problem being analyzed. Estimates use VECM to analyze the data collected. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Li et al [11] observed that financial market deepening and financial institutional deepening have an adverse effect on environmental quality by increasing the amount of CO 2 e in BRICS countries from 1990 to 2019. Aminata et al [51] found positive effects of GDP and population on CO 2 e by using the vector error correction model in China and India from 1984 to 2014 at shorter and longer scales, whereas [52] found the negative impacts of financial deepening on CO 2 e in GCC countries from 1993 to 2019. Mohsin et al [53] found significant positive and negative relations between GDP and CO 2 e for Europe and Central Asia by using the ARDL method for the duration from 1971 to 2016.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Li et al [11] observed that financial market deepening and financial institutional deepening have an adverse effect on environmental quality by increasing the amount of CO 2 e in BRICS countries from 1990 to 2019. Aminata et al [51] found positive effects of GDP and population on CO 2 e by using the vector error correction model in China and India from 1984 to 2014 at shorter and longer scales, whereas [52] found the negative impacts of financial deepening on CO 2 e in GCC countries from 1993 to 2019. Mohsin et al [53] found significant positive and negative relations between GDP and CO 2 e for Europe and Central Asia by using the ARDL method for the duration from 1971 to 2016.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%